Traveling wavefronts in a reaction–diffusion model with chemotaxis and nonlocal delay effect. (February 2019) - Li, Dong; Guo, Shangjiang
Abstract: This paper is devoted to the study of traveling wavefronts of large wave speed for a reaction–diffusion model with chemotaxis and nonlocal delay effect by applying the perturbation method. The proof relies on an abstract formulation of the wave profile as a solution of an operator equation in a certain Banach space, coupled with the Fredholm theory and the Banach contraction mapping principle. This result is illustrated by an application to the chemotaxis–diffusion–growth model with the logistic source and a single delay effect.